Utilizing Health Informatics as a Means of Assisting in Eliminating Health Disparities in Diverse Populations and Improving Health Care Quality - Enahoro, Queen E. (International Journal of Health Sciences, 2023)
Purpose: Health informatics is the process of collecting, analyzing, and managing health data, as well as applying medical principles in combination with information technology systems to help doctors provide better treatment. Health informatics has however been faced with quite a number of challenges over the past time. Methodology: Overall Patient care and Satisfaction are important methods to measure success in the healthcare industry. This statistic is critical for verifying that present methods and procedures are effective and identifying those that are not and should be changed accordingly. Findings: It is often defined as the achievement of care goals from both a provider and a patient perspective. Measuring patient outcomes yields vast data sets that can be utilized to enhance outcomes in a variety of ways. In this process, health informatics can play a crucial role. Unique Contribution to Theory, Practice and Policy: In the pursuit of improving patient outcomes, professionals may utilize data to detect at-risk patients, streamline procedures, boost productivity, and support research by appropriately gathering, analyzing, and using these figures.